DIAGNOSIS AND TREATMENT OF ACUTE STREPTOCOCCAL PHARYNGITIS IN CHILDREN - T. V. Kulichenko (Pediatričeskaâ Farmakologiâ, 2015)
Acute streptococcal pharyngitis is diagnosed in 15–30% of the patients seeking medical advice for fever and sore throat. The local infection is usually mild/moderate; however, it may result in severe purulent and immunopathological complications. Despite high incidence and prevalence of the disease, the issues of diagnosis and treatment of streptococcal tonsillitis and pharyngitis remain highly discussable. The literature review presents information on the modern diagnostic principles, potential of using express tests to detect Streptococcus pyogenes infection and selection of antibacterial therapy of acute streptococcal pharyngitis based on the data of evidence-based studies and systemic reviews. The article emphasizes the most discussable issues of treatment, including antibiotic therapy pattern, and effectiveness of tonsillectomy in the event of chronic or recurrent tonsillitis.